Determination of first order rate constants for wetlands treating livestock wastewater in cold climates. Issue 1 (1st January 2007) - Jamieson, Rob; Gordon, Robert; Wheeler, Natalie; Smith, Erin; Stratton, Glenn; Madani, Ali
Abstract : Four years of performance data from a free-water surface constructed wetland receiving dairy wastewater in Nova Scotia was used to compute first order reaction rate constants ( K a ) for several parameters including BOD5, TP, TKN, NH4 + -N, FC, and TSS. Flow rates at the inlet and outlet of the 5 m wide × 20 m long wetland were continuously measured to assess how external hydrologic influences affected the water budget of the wetland and the system treatment performance. The K a values were calculated using inlet and outlet concentrations and an assumption of plug flow hydraulics. Adjusted rate constants ( K ac ) were also computed, in which the effects of dilution and concentration on pollutant concentrations were considered. Precipitation, runoff, and evapotranspiration had a large influence on the wetland water budget. Values of K a were higher than K ac for all wastewater parameters, illustrating the effects of dilution on outlet pollutant concentrations and the importance of accurately characterizing wetland hydrology when determining or using rate constants. The K ac values did not appear to be influenced by temperature or solar radiation, but were positively correlated with the hydraulic loading rate for most parameters. Rate constants were lower than those reported in the literature for livestock wastewater treatment wetlands operating in warmer climates. This could be due to differences in climate, but could also be attributed to the relatively high strength wastewater and low hydraulic loading rate (0.1 m month –1 ) used in this study. Key words: treatment wetlands, cold climate, agricultural wastewater, design, rate constants.